Porcine transient receptor potential channel 1 promotes adipogenesis and lipid deposition - Yu Fu; Xin Hao; Jingru Nie; Peng Shang; Xinxing Dong; Bo Zhang; Dawei Yan; Hao Zhang (Journal of Lipid Research)
Adipose tissue, an important organ involved in energy metabolism and endocrine, is closely related to animal meat quality and human health. Transient receptor potential channel 1 (TRPC1), an ion transporter, is adipocytes’ major Ca2+ entry channel. However, its function in fat deposition is poorly understood, particularly in pigs, which are both an ideal model for human obesity research and a primary meat source for human diets. In the present investigation, our findings demonstrate a prominent expression of TRPC1 within the adipose tissue of pigs with a strong fat deposition ability. Functional analysis showed that TRPC1 promotes primary preadipocyte proliferation and adipogenic differentiation. In vivo, transgenic mice expressing porcine TRPC1 exhibited aggravated high-fat diet–induced obesity, hepatic steatosis, and insulin resistance. Moreover, TRPC1 may facilitate adipogenesis via activating phosphatidylinositol 3 kinase/AKT and β-catenin signaling pathways. Our research underscores the pivotal role of porcine TRPC1 as a positive regulator in adipogenesis and lipid accumulation processes, providing a potential target for improving animal meat quality and treating obesity-related diseases in humans.